2017
DOI: 10.29252/ijrm.15.5.265
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of melatonin and ghrelin on spermatogenesis: A narrative review of the literature

Abstract: Spermatocytogenesis starts from lumens of seminiferous cords and after migration to the basal membrane ends to the lumens again. We attempt to review the protective effects of melatonin and ghrelin on Spermatocytogenesis and in particular on spermatogonial stem cells, as two rather newly-discovered hormones. Testicular freezing prior to chemotherapy and radiotherapy is one of the ways of preserving fertility in children with cancer. The freezing has two methods of slow-freezing (cryopreservation) and rapid-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…There is a lot of evidence that show the serious role of oxidative stress in male infertility, which should be considered in examining the causes of male infertility and stages of their treatment ( 5 , 19 , 23 ). Studies have reported high levels of free radicals in 25-40% of infertile men ( 20 , 24 , 25 ). Although the primary pathological mechanisms of testicular damage aren’t fully understood, but oxygen free radicals formed during the ischemia-reperfusion have important role in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lot of evidence that show the serious role of oxidative stress in male infertility, which should be considered in examining the causes of male infertility and stages of their treatment ( 5 , 19 , 23 ). Studies have reported high levels of free radicals in 25-40% of infertile men ( 20 , 24 , 25 ). Although the primary pathological mechanisms of testicular damage aren’t fully understood, but oxygen free radicals formed during the ischemia-reperfusion have important role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches on oxidative stress and produced free oxygen radicals after testicular torsion show that antioxidants can protect testis against ROS damages ( 1 , 3 , 4 , 11 ). Antioxidants play a key role in andrology ( 12 , 13 , 18 - 20 ). Antioxidants are substances that break down the chain oxidative reaction and reduce the oxidative stress ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidences suggesting that the pineal gland secretes melatonin plays an important role in testicular development and spermatogenesis. (Gholami, Ahmadi, Abaszadeh, & Khaki, 2017). Loss of ASMT will impair spermatogenesis and male fertility.…”
Section: Ta B L E 1 Hormone Resultsmentioning
confidence: 99%
“…Shreds of evidence provide that oxidative stress is resulted from physical as psychological stress [26]. In fact, significant studies have demonstrated that protein oxidation is related to the expression of a variety of human diseases as diabetes, atherosclerosis, fertility, and neurodegenerative disorders [27][28][29]. Many antioxidant intervention strategies are available in the organism but currently, new peptides as antioxidants have appeared.…”
Section: Ghrelin Strategies In Reducing Oxidative Stress Processesmentioning
confidence: 99%